When technical solutions are not enough : analysing challenges at delivery in mixed-signal projects inside design houses : Software Engineering research perspective - Vidigal, Tiago Pereira (2022)
Dissertação (Mestrado Profissional em Computação Aplicada) — Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Ciência da Computação, Brasília, 2022.